Exploring Health Systems Within the Context of Social Determinants of Health: A Global Health Case Study - Fredrick, Norman B. (MedEdPORTAL, 2016)
INTRODUCTION: Global health case studies can highlight, often in dramatic fashion, topics such as health disparities, health systems, and the social determinants of health. This resource presents a case study of an adolescent Haitian boy requiring lifesaving heart surgery in the US due to an acquired mitral valve disease from untreated streptococcal pharyngitis. METHODS: While the case begins in a US clinic setting, it then goes on to explore the patient's home context—an impoverished village in rural Haiti—in order to demonstrate the effect of social determinants on both an individual's health and the capacity of health care systems to provide appropriate care. The case study concludes by asking the students to explore which health interventions, from a list of options, they would recommend to improve health in rural Haiti. Students discuss the advantages and disadvantages of developing health initiatives that vary by level of impact and approach. RESULTS: This case study has been presented to two classes of first-year medical students during their Health Systems course and was well received. DISCUSSION: By providing linkages between the local and international contexts, this case provides greater relevance for global health material to all participating students.